Motion, Interaction and Games 2019
DOI: 10.1145/3359566.3364695
|View full text |Cite
|
Sign up to set email alerts
|

A VR Game-based System for Multimodal Emotion Data Collection

Abstract: The rising popularity of learning techniques in data analysis has recently led to an increased need of large-scale datasets. In this study, we propose a system consisting of a VR game and a software platform designed to collect the player's multimodal data, synchronized with the VR content, with the aim of creating a dataset for emotion detection and recognition. The game was implemented ad-hoc in order to elicit joy and frustration, following the emotion elicitation process described by Roseman's appraisal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Alternatively, a study used virtual reality games to assess the CPM across various emotions (Meuleman and Rudrauf, 2018) and found that fear and joy were predicted by appraisal variables better than by other components, whereas these two emotions were generally poorly classified in our study. Other recent studies have also made use of (virtual reality) video games to assess appraisal and other emotion components during brain imaging (Leitão et al, 2020) or physiological (Bassano et al, 2019) measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a study used virtual reality games to assess the CPM across various emotions (Meuleman and Rudrauf, 2018) and found that fear and joy were predicted by appraisal variables better than by other components, whereas these two emotions were generally poorly classified in our study. Other recent studies have also made use of (virtual reality) video games to assess appraisal and other emotion components during brain imaging (Leitão et al, 2020) or physiological (Bassano et al, 2019) measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The same appraisal manipulations are addressed by van Reekum et al (2004) in the context of a simple video game to study physiological reactions. In Bassano et al (2019) a Virtual Reality (VR) game and a software platform collecting the player's multimodal data, synchronized with the VR content, are used to build a dataset. The game used was designed according to the emotion elicitation process described by Roseman's appraisal theory.…”
Section: Related Work Applications Of Appraisal Theoriesmentioning
confidence: 99%
“…While our main aim is to introduce a new self-assessment method in the wild, we also believe that we need to perform more controlled experiments. The different methods of self-assessment can be compared when events (stimuli) that potentially may elicit emotional states are experimentally controlled (e.g., in the virtual environment, see a preliminary work by Bassano et al, 2019). This would allow us to compare the reports provided by different participants about the specific events.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Methods requiring active participation of subjects were also used, e.g., by using video games (Tognetti et al, 2010 ), virtual reality (Ververidis et al, 2008 ) and more recently immersive VR-games (Bassano et al, 2019 ). The latter uses a system composed of a VR-game and software platform to collect the player's physiological data.…”
Section: Common Emotion Elicitation Techniques Used For Data Collementioning
confidence: 99%